The doubled burden of diabetic bone disease: hip fracture and post-hip fracture mortality. Issue 5 (May 2021) - Behanova, Martina; Haschka, Judith; Zwerina, Jochen; Wascher, Thomas C; Reichardt, Berthold; Klaushofer, Klaus; Kocijan, Roland
Abstract : Objective: Patients with diabetes have an increased risk of osteoporosis and shorter life expectancy. Hip fracture (HF) is the most serious consequence of osteoporosis and is associated with increased mortality risk. We aimed to assess the association of antidiabetic medications with HF and the post-hip fracture mortality risk among diabetic patients ≥50 years. Design: In this nationwide case-control study 53 992 HF cases and 112 144 age-, sex- and region-matched non-hip fracture controls were analyzed. A cohort of hip-fractured diabetic patients were followed-up for an all-cause mortality. Methods: We defined three groups of diabetic patients based on a prescription of antidiabetic medications: group 1 treated with insulin monotherapy (G1DM), group 2 (G2DM) treated with blood glucose-lowering drugs (BGLD) only, group 3 on a combined BGLD and insulin therapy (G3DM). We applied logistic regression and Cox regression. Results: We identified 2757 G1DM patients, 15 310 G2DM patients, 3775 G3DM patients and 144 294 patients without any antidiabetic treatment. All three groups of diabetic patients had increased odds of HF compared to controls. G1DM patients aged 50–64 years (aOR: 4.80, 95% CI: 3.22–7.17) and G3DM patients (aOR: 1.39, 95% CI: 1.02–1.88) showed the highest HF odds, whereas G2DM patients had 18% decrease in HF odds than their non-diabetic controls (aOR: 0.82, 95% CI: 0.69–0.99). All diabetic patients had increased post-hip fracture mortality risk compared to non-diabetic controls. The highest mortality hazard was observed in G1DM patients, being greater for women than men (HR: 1.71, 95% CI: 1.55–1.89 and HR: 1.44, 95% CI: 1.27–1.64, respectively). Conclusions: Antidiabetic medications increase the probability of HF. Diabetic patients, who sustained HF have a higher mortality risk than non-diabetic patients.